Robustness in numerical computations of damage evolution in cohesive-frictional materials - de Borst, René (Computer Assisted Methods in Engineering and Science, 2023)
Numerical simulations of the mechanical behaviour of structures composed of cohesive-frictional materials such as soils, concrete and rocks, still suffer from a lack of robustness. Too often an inability to continue the computation beyond a certain level of loading is encountered. Also, predictions of the structural behaviour can be quite inaccurate, with errors amounting up to 100%. Some typical causes for these observations are discussed and some remedies are suggested.